Evolution of Globalised business R&D: Features, drivers, impacts - Pietro Moncada-Paternò-Castello; Peter Voigt; Marco Vivarelli (European Commission, Joint Research Centre (JRC), 2011)
The globalisation of R&D activities has continued to grow as companies are increasingly trying to capture knowledge and market opportunities internationally. The rapid evolution of national economies and the ways to conduct knowledge-intensive businesses has brought researchers and analysts to pursue a deeper understanding of the globalisation of corporate R&D and the related driving factors and impacts. This Working Paper provides an overview of the evolution of globalised business R&D activities and an outline of trends is provided with quantitative information from 2001 to 2009. Thus, the literature on the main drivers and impacts of the research process is reviewed and controversial arguments are discussed and reflected upon in the light of recent empirical observations. In particular, the drivers for firms to undertake R&D in their home country, to internationalise their R&D operations and to select a particular location for R&D implementation are analysed according to both the perspective of S&T supply side and for goods and services demand side. Furthermore, the impact of the internationalisation of business R&D is analysed for firms' host or home countries, with a particular focus on the effects on competitiveness and employment. The conclusions and policy implications from the main results of this work are presented in the last section of the document.
Keywords: F21; F23; L16; O32; 330; Research and Development [R&D]; Business Enterprise Expenditure on R&D [BERD]; internationalisation; innovation; investment gap; R&D policies